Role of renal doppler ultrasonography in evaluating renal haemodynamics in diabetic patients and its correlation with laboratory parameters (serum HbA1C and serum creatinine) - Sharma, Kritika; Thakur, Madhurjya Kumar; Mahela, Sangita; Konwar, Ranjumoni; Varma, Dixit; Ullah, Ibrahim Khalil; Baishya, Nirupam Konwar (International Journal of Research in Medical Sciences, 2023)
Background: Due to high prevalence of Diabetes Mellitus in India, Diabetic nephropathy is on the rise. Diabetic Nephropathy is the leading cause of End stage renal disease and the major factor responsible for renal transplantation. Grey scale ultrasound can detect morphologic renal parenchymal changes late in the disease but the functional haemodynamic changes can be detected early on, by the means of doppler indices such as Resistive Index (RI) and Pulsatility Index (PI). Hence, application of renal doppler can aid in the diagnosis of early nephropathic changes to allow early medical intervention, therefore improving disease prognosis. Methods: Renal doppler ultrasonography was performed in 64 diabetic individuals, in the main renal artery and at the interlobar arteries of both kidneys in the upper pole, interpolar region, and lower pole. RI and PI were obtained for each artery and averaged. The correlation between the Mean RI and Mean PI, each with HbA1c and serum creatinine was checked for every patient using relevant statistical tests. Results: Mean RI and PI in study participants were above the normal range. RI and PI both showed a statistically significant positive correlation with serum creatinine, HbA1c as well as the age of the patient and duration of diabetes mellitus (p<0.001). Conclusions: Evaluation of renal doppler indices while correlating them with laboratory parameters can help slow disease progression. The patient can be provided with medical intervention at the early stage on detection of altered renal indices, hence reducing morbidity and mortality and significantly improving disease prognosis and outcome.